2010
DOI: 10.1523/jneurosci.3394-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Form of Noradrenergic-Dependent Respiratory Motor Plasticity Triggered by Vagal Feedback

Abstract: The respiratory control system is not just reflexive, it is smart, it learns, and, in fact, it has a memory. The respiratory system listens to and carefully remembers how previous stimuli affect breathing. Respiratory memory is laid down by adjusting synaptic strength between respiratory neurons. For example, repeated hypoxic bouts trigger a form of respiratory memory that functions to strengthen the ability of respiratory motoneurons to trigger contraction of breathing muscles. This type of respiratory plasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 64 publications
(90 reference statements)
4
45
0
Order By: Relevance
“…Comparison of the above data for paralyzed and mechanically ventilated rats (Figures 2, 3, 5, and 6) vs. nonparalyzed and spontaneously breathing rats (Figure 7) showed that hLTF was effectively induced by repetitive no-lung-inflations (by stopping the ventilator or by airway occlusion) in both cases. This is consistent with the previous finding that repetitive interruption of vagally mediated lung volume feedback alone could induce hLTF (24). However, in spontaneously breathing rats (with vagi intact), GG activity also exhibited a significant tonic (respiratory phase-spanning) component during (but not before) airway obstruction ( Figure 7, B-D).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Comparison of the above data for paralyzed and mechanically ventilated rats (Figures 2, 3, 5, and 6) vs. nonparalyzed and spontaneously breathing rats (Figure 7) showed that hLTF was effectively induced by repetitive no-lung-inflations (by stopping the ventilator or by airway occlusion) in both cases. This is consistent with the previous finding that repetitive interruption of vagally mediated lung volume feedback alone could induce hLTF (24). However, in spontaneously breathing rats (with vagi intact), GG activity also exhibited a significant tonic (respiratory phase-spanning) component during (but not before) airway obstruction ( Figure 7, B-D).…”
Section: Resultssupporting
confidence: 92%
“…Because the hLTF so induced has been shown to be mediated mainly by repetitive interruption of lung volume feedback independently of 5-HT 2 receptors and without accompanying long-term facilitation of diaphragm activity (24), it was distinct from the 5-HT 2 receptor-dependent hLTF induced by repetitive hypoxia (30), although a minor contribution of the latter effect cannot be ruled out. Given that patients with OSA often experience only hypopnea (with partial airway obstruction and less severe resultant decreases in blood oxygen saturation and increases in hypoxic stimulation), the hLTF attained in this case may be weaker than that resulting from complete obstructive apnea, making this second-line motor defense against OSA even less effective during sleep.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations